Blade Runner 2019. 2, Off world - Green, Michael (Screenwriter); Johnson, Mike (Comic book author) (Titan Comics, 2020)
"In 2019, the Blade Runner known as Aahna 'Ash' Ashina rescued Cleo Selwyn, daughter of business tycoon Alexander Selwyn, from a plot to give the girl to the Tyrell Corporation for genetic experimentation. Ash and Cleo escaped Los Angeles and disappeared. Now, seven days later and living under assumed identities, Ash and Cleo have resurfaced on one of the Off-world mining colonies. But Cleo's father has never stopped looking for them, sending out dozens of bounty hunters and search parties to kill Ash and bring his daughter home. Now, following a bloody Replicant mutiny, Ash and Cleo have become separated and ruthless new Blade Runner called Hythe has Ash dead in her sights."--Provided by publisher.